Migration, Co-ordination Failures and EU Enlargement - Tito Boeri; Herbert Brücker (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
EU leaders are well aware of the relevance of migration in the European policy agenda. Thirty-two pages out of forty-eight of the Presidency Conclusions at the November 2004 European Council were devoted to migration policies. Economic theory suggests that there is a strong case for policy co-ordination in this field: relevant spillovers across national jurisdictions, economies of scale and potential free-riding in the enforcement of border controls. However, no delegation of authority to supra-national bodies is envisaged in the Presidency Conclusions in the field of restrictions to legal migration. While Qualified Majority Voting is now accepted on measures tackling illegal migration, decisions on restrictions to legal migration are envisaged only under unanimity rules.
Keywords: 330